Nalle-Karhu ; Mielummin kanssas rokkaisin - Loukiala, Pekka, 1944-2010; Scandia-Musiikki ([Helsinki] : Scandia, 1974)
2 kappaletta.
Pekka Loukiala (lauluääni), yhtye.
Keywords: Loukiala, Pekka, -- 1944-2010 -- singlet